Sekundärnutzung von Sozial- und Gesundheitsdaten Rechtliche Rahmenbedingungen - Dierks, Christian (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2020)
"Much of the data collected in the statutory health insurance system is of great value for the further development and improvement of health care. Social and health data as personal data are also subject to a tight legal framework in terms of data protection law. Their use in other contexts requires a deep understanding of the regulations at European and national level. This volume provides an overview of the current legal framework and an important orientation for the legally secure use of social and health data. The plant makes it possible to develop solutions and products that improve the quality of care. The first part sets out the social law framework for the use of social data for research. The second part provides an overview of how research data is handled after the application of the GDPR and corresponding national adjustments to the legal framework."